Free and forced oscillations modeling of shell structures with compartments - Стрельнікова, О. О.; Сєрікова, О. М.; Науменко, Ю. (My University, 2023)
The purpose of this study is to analyze free and forced vibrations of shells of rotation with an arbitrary meridian and internal partitions installed to dampen sloshing.
Keywords: oil tanks; sloshing; stability; boundary and finite element methods; flammable liquids; earthquakes; seismic loads